Activation of FGD5-AS1 Promotes Progression of Cervical Cancer through Regulating BST2 to Inhibit Macrophage M1 Polarization - Guokun Liu; Xuan Du; Li Xiao; Qing Zeng; QianLing Liu (Journal of Immunology Research)
Accumulating evidence has elucidated the biological function of lncRNAs in various tumors. FGD5 antisense RNA 1 (FGD5-AS1) is identified as a significant tumor regulator in malignancies. Up to now, the detailed function of FGD5-AS1 in cervical cancer and its underlying molecular mechanisms remain uninvestigated. Bone marrow stromal cell antigen 2 (BST2) can play critical roles in immune response, and the roles of BST2 in cervical cancer was explored currently. The level of FGD5-AS1 and BST2 was detected by qRT-PCR in cervical cancer cells. FGD5-AS1 and BST2 expression was significantly upregulated in cervical cancer cells. Then, the decrease of FGD5-AS1 greatly repressed cervical cancer cell growth in vitro. In addition, FGD5-AS1 silencing repressed BST2 expression and suppressed M2 macrophage polarization. Mechanistically, we confirmed that FGD5-AS1 sponged miR-129-5p to reduce its inhibition on BST2. Furthermore, lack of BST2 depressed cervical cancer cell growth, while inducing apoptosis. Loss of BST2 induced M1 macrophage polarization while blocking M2 macrophage polarization. For another, we demonstrated that FGD5-AS1-triggered M2 macrophage polarization was remarkably reversed by miR-129-5p via suppressing BST2. In conclusion, FGD5-AS1 induced M2 macrophage polarization via sponging miR-129-5p and modulating BST2, thus contributing to cervical cancer development. Our findings revealed FGD5-AS1/miR-129-5p/BST2 as a new potential target for cervical cancer.